2020
DOI: 10.3390/ijms21239019
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Strategies of Halophytic Barley Hordeum marinum ssp. marinum to High Salinity and Osmotic Stress

Abstract: The adaptation strategies of halophytic seaside barley Hordeum marinum to high salinity and osmotic stress were investigated by nuclear magnetic resonance imaging, as well as ionomic, metabolomic, and transcriptomic approaches. When compared with cultivated barley, seaside barley exhibited a better plant growth rate, higher relative plant water content, lower osmotic pressure, and sustained photosynthetic activity under high salinity, but not under osmotic stress. As seaside barley is capable of controlling Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 84 publications
(116 reference statements)
2
16
0
Order By: Relevance
“…Interestingly, it seems that for some DHNs, there is preference for some architectures by stress. We investigated, for instance, the changes in expression under salt stress of different architectures in the leaves, shoots, and roots of three species ( Puccinellia tenuiflora Eutrema salsugenium, and Hordeum marinum ), according to the previously reported studies [ 50 , 51 , 52 ]. As shown in Figure 5 , YnSKn dehydrins are significantly more induced by salt stress than SKn in Puccinellia tenuiflora in leaves and roots with log2-fold changes reaching up to 5.63 and 3.44, respectively ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it seems that for some DHNs, there is preference for some architectures by stress. We investigated, for instance, the changes in expression under salt stress of different architectures in the leaves, shoots, and roots of three species ( Puccinellia tenuiflora Eutrema salsugenium, and Hordeum marinum ), according to the previously reported studies [ 50 , 51 , 52 ]. As shown in Figure 5 , YnSKn dehydrins are significantly more induced by salt stress than SKn in Puccinellia tenuiflora in leaves and roots with log2-fold changes reaching up to 5.63 and 3.44, respectively ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Expression data were collected from the previous reports [ 50 , 51 , 52 ]. Using gene IDs available in these studies, we have identified the protein sequences of dehydrins in the Phytozome v13 database and determined their architectures by using MEME.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The osmotic stress is due to the loss of cellular water content, caused by Na + and Clions accumulation (ion toxicity). These ions are the main contributors to the cellular osmotic potential, and they have to be compartmentalized and sequestrated into vacuoles or endosomal compartments by ion exchangers and the H + pumps localized in the tonoplast or endosomal membranes (Isayenkov et al 2020). This subsequently limits nutrient uptake and photosynthetic assimilation by crops to increase productivity (Xue et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that certain genes were found to express differentially in response to salinity, and these genes might code for transcription factors, or were proposed to be related to primary metabolism, endocytosis, hormonal pathways, and transporters. Isayenkov et al investigated strategies for adaptation to salinity in seaside barley, using nuclear magnetic resonance imaging associated with multi-omics approaches [ 2 ]. The authors proposed that seaside barley has developed specific mechanisms involving the capability to regulate concentrations of Na + and Cl − in leaves and morphological and physiological adaptations of roots when subjected to salinity stress.…”
mentioning
confidence: 99%